Tertiary Enamides as Versatile and Valuable Substrates to Reach Chemical Diversity - Beltran, Frédéric; Miesch, Laurence (Synthesis, 2020)
Tertiary enamides display versatile reactivity and great stability compared to their enamine congeners. This review covers progress made in the development of new methods involving the enaminic reactivity of tertiary enamides with respect to the synthesis of complex nitrogen-containing compounds. A focus on the preparation of biologically active molecules is also presented. The syntheses reported herein are classified based on their reaction type. In addition, mechanistic insights are given for most of the new transformations.1 Introduction2 [2+2] Cycloadditions3 [4+2] Cycloadditions4 Electrocyclizations and Cycloisomerizations5 Sigmatropic Rearrangements6 Nucleophilic Additions7 Tertiary Enamides as Electrophiles8 Cross-Coupling Reactions9 Tertiary-Enamide-Assisted Reactions10 Conclusion and Perspectives
Keywords: tertiary enamides; N-heterocycles; cycloadditions; pericyclic reactions; nucleophilic additions; cross-coupling reactions; tertiary-enamide-assisted reactions